Pengaruh Literasi Keuangan dan Pendidikan Keuangan Keluarga terhadap Perilaku Pengelolaan Keuangan pada Mahasiswa Pendidikan Ekonomi di Samarinda - Anggraini, Beta; Riyadi, Riyo; Sutrisno, Sutrisno (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This research aims to find out whether financial literacy influences financial management behavior, whether family financial education influences financial management behavior, and whether financial literacy and family financial education simultaneously influence financial management behavior among Economic Education students in Samarinda. This research uses a quantitative approach with the type of research being explanatory research. The population in this study were all students of the Economic Education Study Program at Mulawarman University class of 2021 and all students of the Economic Education Study Program at the PGRI Kaltim Teacher Training and Education Institute class of 2021. The sampling technique in this study used a saturated sample with a total sample of 134. Collection technique data carried out using tests and questionnaires. Hypothesis testing used the t test, F test and determination test (R2) while to analyze the data using multiple linear regression analysis using the SPSS version 26 program. The results showed financial literacy variable partially has a positive and significant influence on students' financial management behavior. The family financial education variable partially has a positive and significant influence on financial management behavior student. Simultaneously, financial literacy and family financial education have a significant effect on students' financial management behavior.